Personality characteristics of emigrants and re-emigrants with depressive disorders - Олена Петрівна Венгер (ScienceRise, 2015)
Aim. Migration is considered as one of the factors that affect the mental health of the population. The accumulation of psychological and social problems provoke personal transformation reaction and exclusion personality, and considering emigration as a factor that provoke manifestation or exacerbation of endogenous mental diseases. Given the paucity and inconsistency of scientific data on the characteristics of psycho-emotional disorders, and personality characteristics of immigrants, and the almost complete lack of information about re-emigrants, the aim of our work was to study the mechanisms of psychosocial adaptation (de-adaptation) re-emigrants and immigrants, as well as developing programs of social, psychological, psychotherapeutic and mental health support workers. Methods. We used a standardized method of investigating the person (SMIP) for realization of tasks. Result. Results suggest the presence in examined patients of patocharacterological features of hypothymic (disthymic) type. Significant differences were found in terms of fixed scales SMIP test most pronounced in the group of psychogenic depression, the least - organic. In general, immigrants are inherent traits of anxiety and emotional breadth, re-emigrants - schizoidness and apathy. Conclusions. Identified patterns should be considered when developing therapeutic, rehabilitative and preventive measures